Dampak Teknologi Digital Terhadap Pendidikan Islam di SMA Negeri 1 Wanasaba tahun 2023 - Jumaah Jumaah; Emawati Emawati; Musari Musari (Journal on Education, 2023)
This research aims to investigate the impact of digital technology on Islamic education at SMA Negeri 1 Wanasaba in the year 2023. The background of this study outlines the rapid changes in digital technology and how it can affect teaching and learning methods in the context of Islamic education. SMA Negeri 1 Wanasaba was chosen as the focus of the research because it is representative of a secondary education institution in the region. The research method employed is qualitative, utilizing in-depth interviews and observations as data collection techniques. Research participants include teachers and students involved in the use of digital technology in the context of Islamic education at the school. Data analysis is conducted through an inductive approach, detailing qualitative findings from interviews and observations. The results of this research encompass a deep understanding of the impact of digital technology on the teaching and learning of Islamic education at SMA Negeri 1 Wanasaba, including challenges and benefits arising from the integration of technology. The implications of this research include recommendations for curriculum development, teacher training, and the management of technological infrastructure in the Islamic education environment. By understanding the impact of digital technology, it is hoped that SMA Negeri 1 Wanasaba and similar educational institutions can maximize its positive potential and address potential challenges. This research contributes to a contextual understanding of technology adaptation in Islamic education at the secondary level.